(untitled) (Journal of Health, Population and Nutrition, 2013)
Lead poisoning is a major public-health problem in Bangladesh. A cross-sectional study was conducted to determine the extent of and risk factors for elevated blood lead levels (BLLs) in children in Bangladesh during September 2007July 2009. The study included 919 children aged less than 16 years. The children were recruited from six urban locations in Dhaka and one rural area in Chirirbandar, Dinajpur. In total, 495 (54%) children had high BLLs (>10 ?g/dL), with higher BLLs observed among children aged 5-9 years compared to children of other ages (p<0.001). The BLLs among children in urban Dhaka were significantly higher than those in rural areas (13.45±8.21 ?g/dL vs 7.29±6.25 ?g/dL, p<0.001). The high BLLs correlated with low body mass index (r=-0.23, p<0.001) and low haemoglobin status (r=-0.10, p=0.02). On bivariate analysis, proximity to industry (p<0.001), drinking-water from municipal supply or tubewell (p<0.001), brass or lead water-taps (p<0.001), use of melamine plate (p=0.001), and indigenous medicinal (kabiraji) treatments (p=0.004) significantly correlated with higher BLLs. Proximity to industry and the use of indigenous medicines remained significant predictors of high BLLs after controlling for the confounders. Several risk factors appropriate for future educational interventions to prevent exposure to lead poisoning were identified. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13292 J HEALTH POPUL NUTR 2012 Dec;30(4):404-409